The Quartet : wie vier Frauen die Philosophie zurück ins Leben brachten - Mac Cumhaill, Clare; Wiseman, Rachael; Mac Cumhaill, Clare (C.H.Beck, 2022)
"A vibrant portrait of four college friends-Iris Murdoch, Philippa Foot, Elizabeth Anscombe, and Mary Midgley-who formed a new philosophical tradition while Oxford's men were away at war"--